Non-canonical Targets Mediating the Action of Drugs of Abuse: Cocaine at the Sigma-1 Receptor as an Example - Su, Tsung-Ping (Frontiers in Neuroscience, 2019)
In addition to acting on traditionally recognized receptors or transporters on the plasma membrane, several drugs of abuse including amphetamine, methamphetamine, nicotine, opioid, cocaine, ketamine, and cannabinoid have been shown to exert their effects by acting on additional molecular targets either on the plasma membrane or inside of a cell. Those targets are usually nascent receptors or proteins that can cause downstream signaling or molecular events leading to altered physiological outcomes favoring addictive processes. However, those “non-canonical” targets of drugs of abuse, in general, have not been widely recognized in the drug abuse research. This perspective calls attention to those underrecognized targets with a hope to promote a more complete understanding of the action of drugs of abuse.